Diagnostic Accuracy Of Total Leukocyte Count, Neutrophil Count, And C-Reactive Protein In The Diagnosis Of Acute Appendititis In Children - Dr. Pooja kumari, Dr. Muhammad arshad, Dr. Chen Wen Li, Dr. Payal bai, ⁠Dr. Fnu Shilpa, ⁠Dr. Aisha bakhtiar (South Eastern European Journal of Public Health, 2025)
Objective: Diagnostic accuracy of total leukocyte count, neutrophil count, and c-reactive protein in the diagnosis of acute appendititis in children Patients and methods: A prospective observational study conducted in the Department of Pediatric Surgery, Liaquat National Hospital, Karachi from January 2019 to January 2022. Children admitted with suspected case of acute appendicitis, age ≤16 years, and both males and females were included in this study. Included patients were subjected to carry out c-reactive proteins and complete blood picture including differential leukocyte count and neutrophil count pre-operatively. White blood cell counts of more than 11,000 cells/mm, neutrophil count of more than 75%, c-reactive protein (CRP >0.5 mg/dl were considered positive. Results: A total of 135 patients were included and their mean age was 8.90±2.81 years with a majority of patients were males 69.6% (n = 94). Prevalence of acute appendicitis was 94.07% (n = 127) and patients with mean higher mean neutrophil count and CRP were more likely to have acute appendicitis. Receiver operator characteristics (ROC) shows diagnostic precision of CRP was highest with a sensitivity of 79.5% followed by total leukocyte count (77.2%) and neutrophil count (78.0%) in diagnosing acute appendicitis by using histology as benchmark. Conclusion: The study concluded that there was a predominance of male patients as compared to female patients as observed in the study. CRP and TLC including neutrophilia are valuable markers in acute bacterial infections as they have a positive correlation with each other.